Psychoanalysis : the major concepts - Moore, Burness E.; Fine, Bernard D., 1917- (Yale University Press, 1995)
"In this important book, experts in the field survey current psychoanalytic theory, discussing its principles, technical aspects, clinical phenomena, and applications. The book is both an introduction to and a statement of mainstream American psychoanalysis today and will be a standard reference for psychoanalytic trainees, authors, and teachers." "The book has been designed as a companion volume to Psychoanalytic Terms and Concepts, a glossary edited by Drs. Moore and Fine under the auspices of the American Psychoanalytic Association."--Jacket